Expanding the notion of personal well-being during covid-19 campus closure in India: results from a mixed-methods study with members of higher education - Yeon, G.; Perumbilly, S.; Elangovan, N.; Awungshi, S.; Varghese, K.J. (Asia Pacific Journal of Educators and Education, 2024)
The COVID-19 pandemic has challenged lives globally in unprecedented ways. While numerous studies have discussed the impact of this pandemic on human lives, this descriptive study examined how this pandemic affected personal well-being (PW) for members of Indian higher education in the early phase of the pandemic in 2020 when there were no vaccines and remedies available. Research participants (n = 551) were faculty members, graduate students, and non-teaching staff in Indian higher education. At the time of data collection, when all campuses were closed, all participants were functioning in their roles in the academic communities via virtual platforms. This descriptive study, based on a mixed-methods research design with concurrent triangulation strategies, collected data from all regions of India. Resulting data identified and discussed the impact of the pandemic on six domains of PW in the life of participants: (a) self-care; (b) professional growth; (c) quality of interrelationship within the family; (d) relationships with significant others outside of the family; (e) process of experiencing/facing and addressing challenges; and, (f) relationship with spirituality/transcendental dimensions. The relevance of the last domain may be unique to Indian participants’ socio-cultural context and ethos. The findings and discussion explain how PW is a composite of all these six domains, and the pandemic expanded the notion of PW for the members of Indian higher education. Further, the findings also provided a general orientation on how educational leadership teams and institutions can enhance at least three specific dimensions of their community members and thus increase the likelihood of improving the quality of their professional and personal life. The findings may also have relevance for academic communities worldwide and inform clinicians working with members of academic communities, educational institutions, and policymakers. © Penerbit Universiti Sains Malaysia, 2024.
Keywords: Teacher leadership; dept.mft; distributed leadership; middle leaders; middle leadership; peer-reviewed; teacher leaders

International Dialogue: Our Experience in a Family Therapy Program - Mcdowell, Teresa; Fang, Shi-Ruei; Griggs, Julie; Speirs, Karl; Perumbilly, Sebastian; Kublay, Aliye Ebru (Journal of Systemic Therapies, 2006)
In this paper, we report our experiences as part of an international dialogue group within a U.S. family therapy training program. We describe the dialogue group and share the outcomes of our work together, including our understandings of how global relations, social positions, and personal/cultural characteristics influence our interactions within local contexts. We discuss how participation increased our international awareness and competence, offering two illustrations of how the group helped participants consider family therapy practice and research from a global perspective. Finally, we share the subjective experiences of student group members from the Southern United States, India, Turkey, and South Africa as testimony to the value of cross-national dialogue and to making space for affirming the unique journeys of international learners.
Keywords: dept.mft; peer-reviewed

Viewing the Asian American Experience Through a Culturally Centered Research Lens: Do Scholarship in Family Science and Related Disciplines Fall Short? - Fang, Shi-Ruei Sherry; McDowell, Teresa; Goldfarb, Katia P.; MacDonald, Angella; Perumbilly, Seb; Gonzalez-Kruger, Gloria E. (Marriage & Family Review, 2008)
To better understand and serve Asian-Americans, it is imperative for the family science related fields to take a leadership role in providing in-depth insight into Asian-American families. In this article we report a descriptive analysis of articles published in prominent family-based journals over a 14-year period (1992–2006) relative to their attention to Asian-American families. This study examines the types of research conducted and the knowledge that has been generated about Asian-American families. It also provides a framework for considering future culturally centered research with this population.
Keywords: Asian-Americans; culturally sensitive research approaches; dept.mft; family science; peer-reviewed

Working with Asian Indian American Families: A Delphi Study - Khanna, Anchal; Mcdowell, Teresa; Perumbilly, Sebastian; Titus, Gayatri (Journal of Systemic Therapies, 2009)
In this paper, we contribute to an agenda of developing culturally informed practices, centering specifically on working with Asian Indian and Asian Indian American families. We report the results of a modified Delphi study in which we asked advanced members of the counseling field who are of Asian Indian origin to share their insight relative to family therapy with those who identify as Asian Indian or Asian Indian American in the U.S. Panelists offered a multitude of recommendations, including the importance of: careful assessment that acknowledges within group similarities and differences; attention to extended family ties and intergenerational dynamics; understanding issues of immigration, acculturation, and discrimination; and development of treatment approaches that are congruent with Asian Indian cultural values, beliefs, and practices.
Keywords: dept.mft; peer-reviewed

The Measurement of Outcome Variables in Couple and Family Therapy Research - Sanderson, Jessica; Kosutic, Iva; Garcia, Marisol; Melendez, Tatiana; Donoghue, Jamie; Perumbilly, Sebastian; Franzen, Caroline; Anderson, Stephen (The American Journal of Family Therapy, 2009)
Measurement constitutes a central issue in determining effectiveness of couple and family therapy (CFT). A review of 274 CFT outcome studies published in 25 mental health journals between 1990 and 2005 is presented. Goals of this review were to (1) provide a broad, empirically based overview of CFT outcome research, (2) examine measurement of treatment outcomes, and (3) appraise reporting practices. Findings indicate that a wide range of instruments continue to be used in CFT outcome research, although a foundation for a more integrated and coherent assessment battery has been established. Implications for the field are discussed.
Keywords: dept.mft; peer-reviewed

Transitional Challenges in Technology Adoption among Academic Communities in Indian Higher Education Institutions - N, Elangovan; Yeon, Guydeuk; PERUMBILLY, SEBASTIAN; AWUNGSHI, SARAH HORMEILA (Journal of International Technology and Information Management, 2021)
Keywords: dept.mft; peer-reviewed

Desire on the Inside: Incarcerated bisexual women, identity, and human connection - Smoyer, Amy; Harvey, Rebecca (Queering Desire: Lesbians, Gender and Subjectivity, 2024)
Queering Desire explores, with unprecedented interdisciplinary scope, contemporary configurations of lesbian, bi, queer women’s, and non-binary people’s experiences of identity and desire. Taking an intersectional feminist and trans-inclusive approach, and incorporating new and established identities such as non-binary, masculine of centre (MOC), butch, and femme, this collection examines how the changing landscape for gender and sexual identities impacts on queer culture in productive and transformative ways. Within queer studies, explorations of desire, longing, and eroticism have often neglected AFAB, transfeminine, and non-binary people’s experiences. Through 25 newly commissioned chapters, a diverse range of authors, from early career researchers to established scholars, stage conversations at the cutting edge of sexuality studies. Queering Desire advances our understanding of contemporary lesbian and queer desire from an inclusive perspective that is supportive of trans and non-binary identities. This innovative interdisciplinary collection is an excellent resource for scholars, undergraduate, and postgraduate students interested in gender, sexuality, and identity across a range of fields, such as queer studies, feminist theory, anthropology, media studies, sociology, psychology, history, and social theory. In foregrounding female and non-binary experiences, this book constitutes a timely intervention.
Keywords: dept.mft; dept.swk; peer-reviewed

Handbook of LGBTQ-Affirmative Couple and Family Therapy - Harvey, Rebecca; Murphy, Megan J.; Bigner, Jerry J.; Wetchler, Joseph L. (Routledge, 2021)
This comprehensive second edition inspires therapists to utilize clinical work to pragmatically address intersectional oppressions, lessen the burden of minority stress, and implement effective LGBTQ affirmative therapy. A unique and important contribution to LGBTQ literature, this handbook includes both new and updated chapters reflecting cutting-edge intersectional themes like race, ethnicity, polyamory, and monosexual normativity. A host of expert contributors outline the best practices in affirmative therapy, inspiring therapists to guide LGBTQ clients into deconstructing the heteronormative power imbalances that undermine LGBTQ relationships and families. There is also an increased focus on clinical application, with fresh vignettes included throughout to highlight effective treatment strategies. Couple and family therapists and clinicians working with LGBTQ clients, and those interested in implementing affirmative therapy in their practice, will find this updated handbook essential.
Keywords: dept.mft

Supervised Visitation. - Lynch, Barbara (2000)
Keywords: dept.mft; faculty_collection; sabbatical_report

Normal Madness, Murder and Mayhem - Lynch, J. Edward (Xlibris Corp, 2008)
Keywords: dept.mft; faculty_collection

Nurturing Queer Youth: Family Therapy Transformed - Stone Fish, Linda; Harvey, Rebecca G. (Norton, 2005)
Keywords: Case studies; Case studies; Gay youth; Counseling of; Bisexual youth; Counseling of; Family psychotherapy; Family relationships; Gay youth; dept.mft; faculty_collection

North Star Facilitator's Manual - Manke, Nancy; Matheny, Karla; De Barbieri, Patricia (s.n., 2004)
A program for school-age girls designed to promote social and emotional learning, to enhance resiliency, improve self confidence and aid in the prevention of future problems such as eating disorders, drug abuse and poor academic performance. - p. [1]
Keywords: Self-esteem in women; Study and teaching; Study and teaching; Self-esteem in children; dept.mft; faculty_collection

Collaborating with transgender youth to educate healthcare trainees and professionals: randomized controlled trial of a didactic enhanced by brief videos - Martin, Andrés; Celentano, Jillian; Olezeski, Christy; Halloran, Justin; Penque, Brent; Aguilar, Jemel; Amsalem, Doron (BMC Public Health, 2022)
In collaboration with members of the transgender and gender diverse (TGD) community, we created a didactic resource about the unique needs of TGD youth.
Keywords: Adolescents; Gender-diverse; Health; Health education; Mental health; Transgender; dept.mft; dept.swk; peer-reviewed

Well-Being and Prosperity: Multidirectional Disciplinary Interactions with Religion - Morais, M.; Karakunnel, J.J.; Perumbilly, S.; Yeon, G.; Rassendren, G. (Journal of Dharma, 2022)
Despite significant advancements in science and technology, religion continues to influence human lives. The twentieth-century perspectives from social sciences, influenced by the secular hypothesis, mainly highlight the negative influence of religion on human progress and practically ignore its influential and positive impact on various fields of knowledge/disciplines. In this paper, we have examined literature from politics, economics, and psychology to understand religion’s impact on these disciplines and vice versa. We find that religion’s contribution to human society in the 20th and 21st centuries has been mostly positive, especially in education, healthcare, social justice, economic growth, ethics, and initiatives for eradicating inequality and injustice. For instance, religion provides effective coping measures and strategies when humans face uncertainties and catastrophes and facilitate comfort, confidence, and emotional wellness. Further, we realised that (i) the contemporary research literature in social sciences generally highlights the interaction between religion and various fields of knowledge in a unidirectional way —i.e., religion influencing disciplines and not how disciplines influence religion, and (ii) that it fails to reveal a more complex multidirectional and circular relationship between religion and social sciences. This paper proposes ways to bring together social scientists and religious scholars to facilitate the much-needed discussion on the multidirectional relationship between religion and social sciences, thereby paving the way toward the well-being of individuals and social transformation. © 2022 Journal of Dharma: Dharmaram Journal of Religions and Philosophies (DVK, Bangalore),.
Keywords: and well-being; charitable giving; circularity; dept.mft; linearity; peer-reviewed; political participation; religion; sustainable development; ⛔ No DOI found

Undergraduates and intercultural communication competence: Creating a plan for performance - Madlock, A. (International Journal of Learning, 2009)
Some studies indicate that students develop intercultural communication competence through interaction in multicultural classrooms. However, what happens when classrooms are predominately homogenous and student exposure to other cultures is limited to media representations? It is not uncommon to find this situation still existing on some college campuses in the United States of America, where students have never come in contact with individuals different from themselves, beyond service industry workers, if any contact is made at all. The idea of establishing a significant relationship with someone culturally different is not given any thought. As an instructor of color how does one get students to move beyond their comfort zone and take action to meet individuals that are culturally different outside of the classroom? This paper describes the results of a textual analysis using grounded theory of student writing as they reflect on how to develop and implement effective communication strategies with individuals culturally and ethnically different from themselves outside of the classroom. The results of which might also be used to transform thinking about the diverse community surrounding the university and influence future decision-making on issues of social justice and human equality. © Common Ground, Annette Madlock.
Keywords: Grounded theory; Intercultural communication Competence; Multicultural classroom; Textual analysis; Undergraduates; dept.com; ⛔ No DOI found

Saladin and the truth of religion in Decameron I. 3 and X. 9 - Rhodes, J. (Through a Classical Eye: Transcultural and Transhistorical Visions in Medieval Engl. Italian, and Latin Literature in Honour of Winthrop Wetherbee, 2009)
Keywords: dept.eng

The use of controlled punishment and ritual in couples therapy - Lynch, B.J. (The Therapist's Notebook: Homework, Handouts, and Activities for Use in Psychotherapy, 2013)
Couples who come into therapy with amorphous symptoms often reveal later in treatment that there has been a traumatic event that occurred in the past and that has lingered as a significant disturbance to intimacy. No amount of “talk therapy? or insight seems to allow these couples to move past the point of emotional treachery. This activity is designed to allow these couples a vehicle for putting the past to rest in a way that allows them to continue their relationship without resentment, revenge, or continual pain. © 1998 by The Haworth Press, Inc. All rights reserved.
Keywords: dept.mft

Essential skills in family therapy: From the first interview to termination - Lynch, BJ (American Journal of Family Therapy, 2000)
Keywords: dept.mft; ⛔ No DOI found

Fat in school: applied interdisciplinarity as a basis for consultation in oppressive social context - Clare, Mary M.; Ardron-Hudson, Elise A.; Grindell, Jessica (Journal of Educational and Psychological Consultation, 2015)
Children and youth in schools are subject to the effects of the larger culture's attitudes and values related to body size. When negatively biased, these attitudes and values can have detrimental effects and thus emerge as relevant to educational and psychological consultants. Drawing on the nascent field of Fat Studies with its focus on the cultural meanings attached to large bodies, we identify direct implications of fat phobia for school-age children and youth. Via a brief case example, an initial review of literature, and several examples of health-positive programming, we describe the social justice implications of fat phobia for consultants in school and community settings. In this consideration of the role of consultants for addressing fat bias and supporting health, we also suggest the merit of applied interdisciplinarity as a strong ground for consultation research and practice. The academic area of Fat Studies provides illustration of the integration of disciplinary perspectives (e.g., sociology, anthropology, biology, psychology). Educational and psychological consultation is ideally situated for systematically engaging such interdisciplinarity in support of practical outcomes that are healthy, sustainable, and socially just.
Keywords: dept.mft

Theory into research practice: reflections and recommendations on collaborative feminist research - Harvey, Rebecca G.; Brown, Kristina S.; Miller, Bobbi J.; Williams-Reade, Jacqueline; Tyndall, Lisa; Murphy, Megan J. (Journal of Feminist Family Therapy, 2016)
Six women faculty came together to research their peers asking other women in COAMFTE-accredited programs about their personal and professional identities. The goal of this research was to develop recommendations for the field of Couple/Marriage and Family Therapy to support the engagement and advancement of women faculty. The research collaboration itself became a heuristic, feminist praxis, a co-creation of insight, support network, and professional relationships which had liberating results for the collaborators. We intended to create a research project that would be collaborative, empowering, and transformative for participants; in the process, the collaboration became empowering and transformative for ourselves. This article will reflect on our experiences and provide recommendations for future feminist research teams. Copyright © Taylor & Francis Group, LLC.
Keywords: clinical article; collaboration; dept.mft; family therapy; female; feminism; feminist research; gender; human; insider/outsider; marriage; university

Queer youth in family therapy - Harvey, Rebecca G.; Fish, Linda Stone (Family Process, 2015)
Trends in popular belief about same-sex relationships have undergone noteworthy change in the United States over the last decade. Yet this change has been marked by stark polarizations and has occurred at varying rates depending upon regional, community, racial, religious, and individual family context. For queer youth and their families, this cultural transformation has broadened opportunities and created a new set of risks and vulnerabilities. At the same time, youth's increasingly open and playful gender fluidity and sexual identity is complicated by unique intersections of class, race, religion, and immigration. Effective family therapy with queer youth requires practitioner's and treatment models that are sensitive to those who bear the burden of multiple oppressions and the hidden resilience embedded in their layered identities. We present case examples of our model of family therapy which addresses refuge, supports difficult dialogs, and nurtures queerness by looking for hidden resilience in the unique intersections of queer youths' lives. These intersections provide transformational potential for youth, their families and even for family therapists as we are all nurtured and challenged to think more complexly about intersectionality, sexuality, and gender. Las tendencias en la creencia popular acerca de las relaciones entre personas del mismo sexo han sufrido un cambio considerable en Estados Unidos durante la ultima decada. Sin embargo, este cambio se ha producido a ritmos diferentes segun las comunidades locales y regionales, y el contexto familiar individual. En el caso de los jovenes queer y sus familias, esta transformacion cultural ha ampliado oportunidades y creado un nuevo conjunto de riesgos y vulnerabilidades. Los jovenes queer y sus familias, al intentar desarrollarse en numerosos contextos, estan marcados por divergencias crueles en actitudes y creencias. Al mismo tiempo, la fluidez del genero y la identidad sexual cada vez mas abiertas y ludicas de los jovenes estan complicadas por intersecciones unicas de clase, raza, religion e inmigracion. Una terapia familiar eficaz con jovenes queer exige modelos de tratamiento y profesionales que sean sensibles a aquellas personas que cargan sobre sus espaldas numerosas opresiones y una resiliencia oculta incorporada en sus identidades multiples. Presentamos ejemplos de casos de nuestro modelo de terapia familiar que aborda el refugio, respalda los dialogos dificiles y apoya la sexualidad alternativa buscando la resiliencia oculta en las intersecciones unicas de las vidas de los jovenes queer. Estas intersecciones ofrecen posibilidades transformacionales para los jovenes, sus familias e incluso los terapeutas familiares mientras nos estimulan y nos desafian a todos a pensar de forma mas compleja acerca de la interseccionalidad, la sexualidad y el genero.
Keywords: Adolescent; Family Relations; Family Therapy; Family therapy; Female; Gay; Gender Identity; Homosexuality; Homosexuality, Female; Homosexuality, Male; Humans; Interpersonal Relations; Lesbian; Male; Resilience; Social Identification; Social Isolation; Transgender Persons; Transgendered youth; United States; Vulnerable Populations; Young Adult; adolescent; dept.mft; family relation; family therapy; female; gender identity; homosexuality; human; human relation; lesbianism; male; male homosexuality; procedures; psychology; social behavior; social isolation; statistics and numerical data; transgender; vulnerable population; young adult

Substance abuse prevention: perspectives from india’s addiction treatment professionals - Perumbilly, Sebastian A; Anderson, Stephen A (American Journal of Sociology, 2015)
Keywords: dept.mft; peer-reviewed

Using CBPR methods in college health research exploring excessive alcohol consumption - Bulmer, Sandra Minor; Barton, Barbara A; Liefeld, Julie; Montauti, Sara; Santos, Stephanie; Richard, Melissa; Hnath, Laura; Pelletier, Kara; Lalanne, Jude (Journal of Adolescent Research, 2016)
Community-based participatory research (CBPR) is a collaborative methodology that uniquely involves stakeholders in all stages of the research process. CBPR has been widely utilized in the field of public health, but not widely employed with college populations. This study utilized CBPR methods within a college community to gain insight into excessive alcohol consumption. Six student researchers planned and carried out a rigorous qualitative study at a public university in the Northeast region of the United States. A total of 48 undergraduate participants were recruited for focus groups that were facilitated by two student researchers, and transcribed and analyzed using thematic analysis methods. Students' reasons for drinking alcohol were focused within the themes of inclusion, habitual default, and the student development process. Social media, strict policy/enforcement, and student's desire to avoid responsibility led to increased risk and consequences related to drinking. Students recommended late night transportation and a Good Samaritan policy as strategies to improve student safety. This study led to student advocacy and policy change directed at improving student's health and safety and demonstrated that CBPR methods show promise for engaging students and producing meaningful data.
Keywords: college issues; dept.hhs; dept.mft; emerging adulthood; health; qualitative methods; substance use

Sexual Identity Development and Heteronormativity - Harvey, Rebecca; Stone-Fish, Linda; Levatino, Paul (The Handbook of Systemic Family Therapy, 2020)
Sexual identity development has traditionally been theorized about from within heteronormative societies founded on patriarchal notions with links to misogyny, racism, and classism, among others. These forms of domination have constrained the way sexual identity has been conceived of, researched and written about within the mental health fields and limited the efficacy of clinical work with all people but especially sexual minorities and those who are gender non-binary. In this chapter the authors will deconstruct heteronormativity, examine the deleterious effect of it on mental health, and locate the influence of intersections of oppression on the field of SFT theory and in clinical work. An LGBTQI (lesbian, gay, bisexual, transgender, questioning, intersex) affirmative clinical framework developed from systems theory and queer theory will be outlined, and then a case study using the framework will be described.
Keywords: LGBTQI; dept.mft; dept.swk; family therapy; heteronormativity; marriage and family therapy; sexual identity; systemic family therapy

Facilitators and barriers in treatment seeking for substance use disorders: indian clinical perspectives - Perumbilly, Sebastian A.; Melendez-Rhodes, Tatiana; Anderson, Stephen A. (Alcoholism Treatment Quarterly, 2018)
Despite great advances that have been made in the understanding and treatment of substance use disorders (SUDs), fewer than 11% of eligible patients seek treatment. Few studies have explored the roles of facilitators and barriers in treatment seeking from the perspectives of addiction-focused clinicians working in developing countries. This descriptive study used a mixed-methods research design with concurrent strategies. Research participants were addiction-focused clinicians (N = 112) working in India. Primary research questions examined (1) key facilitators that motivate patients to seek treatment, (2) major barriers in treatment seeking, and (3) critical strategies for enhancing treatment seeking with the support of family, friends, and community. Key facilitators of treatment seeking included informed and caring family members, friends, and community. The most common barriers were patients’ denial of the problem of SUDs, shame in admitting the problem, and belief and confidence that they can quit using substances by themselves anytime. A systemically focused public awareness creation strategy, implemented simultaneously at various key sectors in society, was recommended for facilitating treatment seeking and removing barriers. Implications for clinicians, patients, public health personnel, community leaders, and regional, national, and global policy makers are reviewed. © 2018, © 2018 Taylor & Francis.
Keywords: Addiction treatment; Article; India; adult; aged; awareness; barriers to treatment; clinician; community; dept.mft; drug dependence; facilitators of treatment; female; help seeking behavior; human; male; peer-reviewed; social stigma; substance use disorders; treatment seeking

“To feel him love me”: Emerging intersections of identity, queerness, and differing ability - Harvey, Rebecca (Gender, sex, and sexuality among contemporary youth, 2017)
AbstractOriginality/value This paper provides an alternative approach to nurturing queer identity by (1) creating refuge for emerging sexualities; (2) allowing for difficult dialogues where ability, sexuality, and gender can be pragmatically discussed, performed, and negotiated; (3) tolerating the discomfort of these difficult dialogues and pushing through to nurturing the unique queerness that evolves out of these conversations; and finally (4) encouraging transformation of all participants including client and practitioners. The practitioners discuss their own transformation through the co-created dialog with each other and with the client.
Keywords: Disability; Gay; Gay couple; Intersectionality; Queer; dept.mft; dept.swk

Indian perspectives on treating substance use disorders - Perumbilly, Sebastian A; Anderson, Stephen A (Alcoholism Treatment Quarterly, 2017)
Although research on substance use disorders (SUDs) largely focuses on the developed world, treatment programs from the developing world seldom get international attention. Focusing on India, this study was designed (1) to describe India’s treatment programs, and (2) to report Indian perspectives on critical factors related to treating SUDs. An online survey instrument was created, based on mixed-methods approach with concurrent strategies, to collect data. Participants were India’s clinicians (N = 112). Indian treatment approach suggests that SUDs must be treated by a multidisciplinary treatment team with a comprehensive plan that must include systemically focused clinical interventions in patients’/clients’ relevant relational systems. Findings may have relevance to clinicians, researchers, and policy makers globally. © 2017 Taylor & Francis.
Keywords: Addiction treatment; India; Indian; Note; adult; aged; clinical assessment; comparative study; controlled study; critical factors; dept.mft; drug dependence; family therapy; female; health survey; human; involving families; major clinical study; male; peer-reviewed; professional development; substance use disorders

Parents’ personal growth: expanding the view of therapy for child behavioral problems - Perumbilly, Sebastian A; Anderson, Stephen A; Boylin, William M (Journal of Family Psychotherapy, 2017)
Parenting literature often focuses on parental strategies that promote positive behavioral outcomes for children, but ignores key aspects of parents’ own growth process. This article presents a critical review of current literature on parenting and highlights the importance of focusing on parents’ growth in therapy. A clinical framework to define parents’ growth is offered along with case vignettes and practical guidelines for clinicians in order to assess parents’ growth. © 2017 Taylor & Francis Group, LLC.
Keywords: Article; Couple intimacy; behavior therapy; child behavior; child care; child parent relation; dept.mft; education program; family therapy; growth; human; intimacy; medical literature; parental attitude; parenting; parents’ growth; personal growth; personal needs; practice guideline; problem behavior; responsibility; self care; social isolation; training; vignette

Lesbian couples - Stone Fish, Linda; Harvey, Rebecca (Encyclopedia of couple and family therapy, 2017)
Keywords: Current Political Climate; Difficult Dialogue; Donor Insemination; LGBTQ Community; Lesbian Couple; dept.mft